Mad with Freedom : The Political Economy of Blackness, Insanity, and Civil Rights in the U.S. South, 1840-1940 - Edwards-Grossi, Élodie (Book collections on Project MUSE., 2022)
"Élodie Edwards-Grossi's Mad with Freedom explores the largely unknown social history of racialized theories on insanity in the segregated South. Edwards-Grossi analyzes the medicalization of the Black body from the 1840s until the 1920s, revealing the politicization of science and psychiatric practices, notably concerning notions of citizenship, responsibilities, and civil rights. She begins when theories on insanity started to develop in the 1840s and continues until the 1920s, when they gradually became standardized and emerged as a distinct medical field. In doing so, Edwards-Grossi unites an institutional history of psychiatric spaces in the South that confined Black patients with an intellectual history of early psychiatric theories that defined the Black body as a locus for specific pathologies. Mad with Freedom explores how the use of race in studies on insanity and the brain in the 1840s and 1850s gave birth to politically charged theories on the differential biology and pathologies of white and Black brains. These theories, which emerged predominantly in southern medical schools, gained a second lease on life in the 1860s when anti-abolitionists used them to proclaim that Blacks became insane when confronted with the complexities of freedom, thus politicizing a controversial medical argument. Edwards-Grossi also reveals the localized and subtle techniques of resistance employed later by Black patients to confront medical power by either refusing to work or vocalizing their distress at being categorized as 'Black' and treated as such in these segregated institutions. Her work shows the continuous politicization of science and theories on insanity in the context of Reconstruction and the Jim Crow South. Mad with Freedom explores the gradual evolution of white and Black insanity theories into a more complex and autonomous science--following the standardization of international classifications in the 1890s--which southern asylums and hospitals gradually adopted. The study thus reveals the constant and complex negotiations at stake as physicians operated between the use of standardized categories of diseases and treatments on the one hand and localized, racialized classifications and theories on Black bodies on the other"--